Human factors in land use planning and urban design : methods, practical guidance and applications - Stevens, Nicholas J. (Human factors and socio-technical systems, 2018)
"This book furthers the role of human factors methods in land use planning and urban design that was recognised by Stevens and Salmon in 2014. At a simplistic level the issues found in both discipline areas are one and the same: the design of the environment brings about emergent behaviours that in some cases are not optimal. Such inquiries are often described as humans and systems not behaving as they were expected to; problems which impact overall system performance, and often issues that have been resistant to a range of an ongoing technical interventions. The same is true for many of the challenges in land use planning and design, including crime prevention and safe cities, the prioritisation of walkable and cycleable neighbourhoods, or the design and implementation of enduring, accessible and attractive public open space."